Removal of arsenic from simulated groundwater by adsorption using sequential arrangement of laterite and iron-modified activated carbon - Dang, Son Van (Animo Repository, 2009)
Arsenic is well-known as one of the most toxic elements. Recently, arsenic (As) contamination of groundwater has become a major concern on a global scale, especially in Bangladesh, India and South-East Asia. A promising method that can be considered as an efficient and low-cost method for wide-scale application in rural areas is adsorption, using appropriate, readily available and cheap adsorbents. This study aimed to investigate the removal of arsenic from simulated groundwater using the sequential arrangement of laterite (LA) and iron-modified activated carbon (AC-Fe) in a packed column through experiments and mathematical modelling. Also, other alternative potential adsorbents: LA from Vietnam, rice husk carbon (RH), zero-valent iron (ZVI) and iron oxide (IO) were also investigated to enhance the flexibility and feasibility of application of the arsenic treatment approach developed by this study. The results from batch experiments showed that the Langmuir isotherms and pseudo-second order best described the equilibrium and kinetics of the arsenic adsorption process from simulated groundwater, using LA and AC-Fe under experimental conditions. The adsorption capacities are 0.48 and 1.18 mg/g, respectively. The following appropriate parameters for operation of an adsorption column with diameter of 0.025 m and bed height of 0.5 m are: LA/AC-Fe ratio of 0.3 m/0.2 m, flow rate of 4 to 6 mL/min (or space velocity of 0.98-1.47 m3/m3 h), around neutral pH of 7-8, and initial arsenic concentration of 0.4-0.6 mg/L, corresponding to the breakthrough time of more than 100 hours. The behaviour of the column observed from mathematical modelling was similar to that from column experiments. The breakthrough points from modelling were very close to the experimental ones. The results from this study could facilitate the design of an adsorption column or filter for arsenic treatment using sequential combination of LA and AC-Fe for household use. This could be an efficient and feasible way to remove arsenic from groundwater for ready application in the rural areas, especially in developing and poor countries. The use of the combination of LA and RH-Fe, IO or ZVI is another configuration which can remove arsenic efficiently and flexibly.